Correlation between Red Cell Distribution Width (RDW) with Kidney Function and Hematologic Parameters in Patients undergo Regular Hemodialysis - Hutasuhut, Soraya Mourina; Nasution, Alwi Thamrin; M. Feldy Gazaly Nasution (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2020)
Background. Red cell distribution width (RDW) is a coefficient of variation in red blood cells that can decrease erythropoesis or increase the destructiveness of red blood cells. The objectives of research to determine the relationship of RDW as an inflammatory marker with renal function and hematological parameters in patients undergoing regular hemodialysis Method; Cross sectional research on 20 patients undergoing regular hemodialysis > 3 months in RSUP H Adam Malik Medan. Vital sign, antropometry and venous blood retrieval are performed shortly before hemodialysis. RDW measurement comes from the red blood cell distribution curve in hematological analysis and is an indicator of variation in red blood cell size. Result: out of 20 subjek studies, there were 13 men (65.0%) and 7 (35.0%) women The majority of subjects had comorbid diabetes mellitus 14 (70.0%), hypertension 4 (20.0%). The average length of time patients underwent hemodialysis was 24.45 Â± 20.98 months. There is a significant correlation between RBW and creatinine, Hb, and neutropil (r: 0.519, p:0,019*; r: 0.497, p: 0.026*;r: 0.464, p: 0.039*, respectively) Conclusion: There is a significant relationship between RBW and creatinine, Hb and neutropphils in patients undergoing regular hemodialysis > 3 months.